2013
DOI: 10.1002/jgrb.50179
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake clusters in southern California I: Identification and stability

Abstract: [1] We use recent results on statistical analysis of seismicity to present a robust method for comprehensive detection and analysis of earthquake clusters. The method is based on nearest-neighbor distances of events in space-time-energy domain. The method is applied to a 1981-2011 relocated seismicity catalog of southern California having 111,981 events with magnitudes m ≥ 2 and corresponding synthetic catalogs produced by the Epidemic Type Aftershock Sequence (ETAS) model. Analysis of the ETAS model demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
339
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(366 citation statements)
references
References 60 publications
18
339
0
9
Order By: Relevance
“…(1). We note that Zaliapin and Ben-Zion (Zaliapin and Ben-Zion 2013a) have observed that for earthquake sequences in southern California DM follows an almost uniform distribution in the range [0,2] with an exponential tail for larger values of DM, thus supporting the value hDMi = 1.1 which has been found (Zaliapin and Ben-Zion 2013a) in the observed seismicity of southern California. They have also identified (Zaliapin and Ben-Zion 2013b) that there exist two basic types of earthquake clustering: the burst-like sequences which are consistent with highly brittle behaviour and the swarm-like sequences consistent with mixed brittle-ductile behaviour.…”
Section: A Model For the Explanation Of Båth Lawsupporting
confidence: 82%
See 3 more Smart Citations
“…(1). We note that Zaliapin and Ben-Zion (Zaliapin and Ben-Zion 2013a) have observed that for earthquake sequences in southern California DM follows an almost uniform distribution in the range [0,2] with an exponential tail for larger values of DM, thus supporting the value hDMi = 1.1 which has been found (Zaliapin and Ben-Zion 2013a) in the observed seismicity of southern California. They have also identified (Zaliapin and Ben-Zion 2013b) that there exist two basic types of earthquake clustering: the burst-like sequences which are consistent with highly brittle behaviour and the swarm-like sequences consistent with mixed brittle-ductile behaviour.…”
Section: A Model For the Explanation Of Båth Lawsupporting
confidence: 82%
“…The nearest-neighbour, which is called the parent, can be the parent of multiple events which are called offsprings. We should note that each possible parent-offspring pair is assigned a corresponding distance n but the nearestneighbour is defined as the pair with minimum n ij (Zaliapin et al 2008;Zaliapin and Ben-Zion 2013a). Normalizing the time and space distances by the magnitude of the parent, we have (Zaliapin et al 2008;Zaliapin and Ben-Zion 2015) …”
Section: Second Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These triggering processes by which one earthquake induces (dynamic or static) stress changes leading to potentially multiple other earthquakes [4][5][6][7] are at the core relaxation processes [8]. A specific example of triggering are aftershocks following a large earthquake [9][10][11][12][13]. These aftershocks obey certain empirical laws that characterize, for example, their spatio-temporal distribution, as is the case for the Omori-Utsu (OU) relation [14].…”
mentioning
confidence: 99%